The value of soaking whole sorghum grain for finishing fall pigs in drylot - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Two lots of pigs were self-fed, free choice, whole sorghum grain and a mixed protein supplement. Each lot contained 10 pigs. In one lot, the whole sorghum grain was fed dry, in the other, it was automatically fed into water warmed enough to prevent freezing. The protein supplement fed both lots consisted of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. To each ton of supplement was added 27 pounds of antibiotic Aurofac (Aureomycin) and one half pound of zinc oxide.
Keywords: Swine; Sorghum grain; Drylot; Protein